Implementation of Academic Supervision by School Principals to Improve Teacher’s Performance - Kamsiti, Kamsiti; Putra, Alhadi Yan; Wardiah, Dessy (Journal of Social Work and Science Education, 2024)
The objectives of this research: 1) Describe the implementation of academic supervision by the school principal to improve the performance of teachers at SMP Negeri 4 Air Sugihan, Ogan Komering Ilir Regency; 2) Describe the principal’s strategy for optimizing the implementation of academic supervision to improve teacher performance at SMP Negeri 4 Air Sugihan, Ogan Komering Ilir Regency; 3) Describe the obstacles experienced by school principals in carrying out academic supervision activities to improve teacher performance at SMP Negeri 4 Air Sugihan, Ogan Komering Ilir Regency. This research was carried out at SMP Negeri 4 Air Sugihan, Ogan Komering Ilir Regency with the number of informants being 7 teachers from SMP Negeri 4 Air Sugihan, Ogan Komering Ilir Regency. Data collection techniques use observation, interviews, and documentation studies. The data analysis technique for this research is descriptive qualitative. The results of this research: 1) The implementation of academic supervision by the principal to improve the performance of teachers at SMP Negeri 4 Air Sugihan, Ogan Komering Ilir Regency has been carried out well; 2) strategy for implementing academic supervision activities, the principal has carried out pre-observation activities, planned academic supervision activities, carried out activities, carried out evaluations and follow-up and has involved fellow teachers being supervised; 3) The obstacle experienced by the school principal in carrying out academic supervision activities is that there are official matters which sometimes make the principal unable to carry out his duties as a supervisor at the school so that the task of carrying out academic supervision activities is delegated to other teachers who are colleagues of the teacher who will be supervised.